End of millennium - Castells, Manuel (Oxford Blackwell Publishers, 2010)
This final volume in Manuel Castells' trilogy, with a substantial new preface, is devoted to processes of global social change induced by the transition from the old industrial society to the emerging global network society.
Includes bibliographical references (p. [399]-432) and index
Keywords: Social history -1970-